STUDI DESKRIPTIF HASIL KARYA MENGGAMBAR DITINJAU DARI KARAKTERISTIK SENI RUPA ANAK SEKOLAH DASAR KELAS IIA SDN 19 KOTA BENGKULU: Penelitian deskriptif - Dwi Aria Nopela; Pebrian Tarmizi; Yuli Amaliyah (STKIP Subang, 2025)
This study aims to describe the results of drawing works in terms of the characteristics of elementary school children's art in class IIA of SDN 19 Bengkulu City. The type of research used is qualitative using a descriptive method. The research subjects are the six students of class IIA and the class IIA teacher. Data collection techniques include observation, interviews, and documentation. Data analysis techniques involved data collection, data condensation, data presentation, and drawing conclusions. Data validity was ensured through credibility testing using triangulation techniques and member checks. The results of this study indicate that the children's drawings exhibit X-ray patterns, lying patterns, bird's eye patterns, realistic patterns, and overlapping patterns. The conclusion of this study is that the six drawings created by the students follow the characteristics of elementary school children's visual art, namely: (1) displaying X-ray patterns, (2) displaying lying patterns, (3) displaying bird's-eye patterns, (4) displaying realistic patterns, (5) displaying overlapping patterns.